2023
DOI: 10.3847/1538-4357/acd692
|View full text |Cite
|
Sign up to set email alerts
|

Warm Molecular Gas in the Central Parsecs of the Buried Nucleus of NGC 4418 Traced with the Fundamental CO Rovibrational Absorptions

Abstract: We investigated the inner buried nucleus of a nearby luminous infrared galaxy, NGC 4418, using high-resolution spectroscopy of fundamental carbon monoxide (CO) rovibrational absorptions around 4.67 μm for the first time. This method allowed us to examine the physical and kinematical properties in the hot inner region of this nucleus. We detected a series of both very deep (partly saturated) 12CO and moderately deep (optically thin) 13CO absorption lines and inferred a large column density (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…Rich et al (2023) previously reported the detection of the ν 2 14.0 μm band of HCN and the ν 5 13.7 μm band of C 2 H 2 in absorption toward the NE core in VV 114E. The fundamental band of CO at 4.67 μm, tracing transitions between the ground state and the first vibrationally excited state, has been observed in absorption toward several heavily obscured U/LIRGs from the ground (e.g., Spoon et al 2003;Geballe et al 2006;Shirahata et al 2013;Baba et al 2022;Ohyama et al 2023). Pereira-Santaella et al (2024) demonstrated JWST's capabilities for studying the CO band in emission.…”
Section: Introductionmentioning
confidence: 97%
“…Rich et al (2023) previously reported the detection of the ν 2 14.0 μm band of HCN and the ν 5 13.7 μm band of C 2 H 2 in absorption toward the NE core in VV 114E. The fundamental band of CO at 4.67 μm, tracing transitions between the ground state and the first vibrationally excited state, has been observed in absorption toward several heavily obscured U/LIRGs from the ground (e.g., Spoon et al 2003;Geballe et al 2006;Shirahata et al 2013;Baba et al 2022;Ohyama et al 2023). Pereira-Santaella et al (2024) demonstrated JWST's capabilities for studying the CO band in emission.…”
Section: Introductionmentioning
confidence: 97%

The CO-to-H2 conversion factor of molecular outflows

Pereira-Santaella,
González-Alfonso,
García-Bernete
et al. 2024
A&A